2010
DOI: 10.1002/cne.22443
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic innervation of the ileocecal junction in horses

Abstract: The distribution and chemical phenotypes of sympathetic and dorsal root ganglion (DRG) neurons innervating the equine ileocecal junction (ICJ) were studied by combining retrograde tracing and immunohistochemistry. Immunoreactivity (IR) for tyrosine hydroxylase (TH), dopamine beta-hydroxylase (DBH), neuronal nitric oxide synthase (nNOS), calcitonin gene-related peptide (CGRP), substance P (SP), and neuropeptide Y (NPY) was investigated. Sympathetic neurons projecting to the ICJ were distributed within the celia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 94 publications
2
40
0
Order By: Relevance
“…The discrepancy concerning the paravertebral ganglia may result from different lengths of the examined gastrointestinal tract sections in these tracing experiments. Although the neurons of the sympathetic trunk ganglia are considered to control the blood flow within the gastrointestinal tract, a tracing study on the innervation of the ileocecal junction in horses disclosed only solitary perikarya in the last three thoracic sympathetic chain ganglia (Russo et al, 2010). This observation seems to be particularly suggestive in view of the anatomy of the ileocecal junction in horses, which appears as an angio-muscular system with dense submucosal venous plexus (Kotze, 1988(Kotze, , 1990.…”
Section: Distribution Of Traced Neuronsmentioning
confidence: 94%
“…The discrepancy concerning the paravertebral ganglia may result from different lengths of the examined gastrointestinal tract sections in these tracing experiments. Although the neurons of the sympathetic trunk ganglia are considered to control the blood flow within the gastrointestinal tract, a tracing study on the innervation of the ileocecal junction in horses disclosed only solitary perikarya in the last three thoracic sympathetic chain ganglia (Russo et al, 2010). This observation seems to be particularly suggestive in view of the anatomy of the ileocecal junction in horses, which appears as an angio-muscular system with dense submucosal venous plexus (Kotze, 1988(Kotze, , 1990.…”
Section: Distribution Of Traced Neuronsmentioning
confidence: 94%
“…Specificity of anti-SP and anti-nNOS antibodies as well as the IB4 used in this study, have already been tested earlier (Russo et al, 2010;2011). The anti-NF200 antibody (Sigma-Aldrich, N4142) utilized in this study was tested for its specificity by Western blot (WB) analysis (Fig.…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…Previous studies have shown the presence of NOS in the enteric ganglia and muscle fibers under various conditions, such as malnutrition and renutrition [27,28] , ischemia and reperfusion [29][30][31] and obesity [32,33] . The enteric neurons of the ICJ stain positive for NOS, PGP 9.5, and c-kit [3,4,6,8] . Additionally, neuronal nitric oxide synthase (nNOS) is present in the myenteric, the submucosal ganglia and the IJC muscle layers in horse [8] .…”
Section: Semmentioning
confidence: 99%
“…The enteric neurons of the ICJ stain positive for NOS, PGP 9.5, and c-kit [3,4,6,8] . Additionally, neuronal nitric oxide synthase (nNOS) is present in the myenteric, the submucosal ganglia and the IJC muscle layers in horse [8] . In our study, we noticed the presence of NOS in the muscle layers and neurons in the ICJs of both the young and elderly groups, but we did not observe a difference in the intensity of the stain for HuC/D or NOS between groups.…”
Section: Semmentioning
confidence: 99%
See 1 more Smart Citation